Psychobiotic Lactobacillus plantarum JYLP-326 relieves anxiety, depression, and insomnia symptoms in test anxious college via modulating the gut microbiota and its metabolism - Zhu, Ruizhe; Fang, Yilin; Li, Hongyu; Liu, Ying; Wei, Jing; Zhang, Shuwei; Wang, Liwei; Fan, Rui; Wang, Lingfang; Li, Shengjie; Chen, Tingtao (Frontiers in Immunology, 2023)
Test anxiety frequently occurs in college students and harms their physical and psychological health, but suitable interventions or therapeutical strategies are still missing. The present study aims to evaluate the potential effects of Lactobacillus plantarum JYLP-326 on test anxious college students. Sixty anxious students were enrolled and randomly allocated to the placebo group and the probiotic group, which were instructed to take placebo and JYLP-326 products twice per day for three weeks, respectively. Thirty unanxious students with no treatments were assigned to a regular control group. The anxiety, depression, and insomnia questionnaires were used to measure students’ mental states at the baseline and the end of this study. 16S rRNA sequencing and untargeted metabolomics were performed to analyze the changes in the gut microbiota and fecal metabolism. The questionnaire results suggested that JYLP-326 administration could relieve the symptoms of anxiety, depression, and insomnia in test anxious students. The gut microbiomes of the placebo group showed a significantly greater α diversity index than the control group (p < 0.05). An increased abundance of Bacteroides and Roseburia at the genus level was observed in the placebo group, and the relative abundance of Prevotella and Bifidobacterium decreased. Whereas, JYLP-326 administration could partly restore the disturbed gut microbiota. Additionally, test anxiety was correlation with disordered fecal metabolomics such as a higher Ethyl sulfate and a lower Cyclohexylamine, which could be reversed after taking JYLP-326. Furthermore, the changed microbiota and fecal metabolites were significantly associated with anxiety-related symptoms. These results indicated that the intervention of L. plantarum JYLP-326 could be an effective strategy to alleviate anxiety, depression and insomnia in test anxious college students.